The Principle of Good Faith in Contractual Relations - Tamar Mepharishvili (European Scientific Journal, ESJ, 2025)
The principle of good faith obligates the parties to act in good faith both during the conclusion of the contract and throughout its performance. This obligation means that neither party should harm the other solely to gain benefits from the contract. The significance of the principle of good faith is underscored by the fact that it is a fundamental principle in modern law, philosophy, and business, forming the basis of contractual relationships in most legal systems, including French, German, and others. In contrast, in English law, the principle of good faith was only recently introduced through various statutes and conventions. This article does not propose creating a new concept regarding the principle of good faith but rather offers a coherent explanation and approach to understanding and interpreting the concept. Given the scope of the topic, it is impossible to exhaustively address this issue within the format of this article. The aim is to examine the peculiarities of applying the principle of good faith in contractual relationships within various legal systems and, most importantly, to address issues regarding its justification, as the issue of justification reflects the state of both the legal culture of the country and the development of justification techniques. The research primarily employs comparative law and analytical methods. Using the comparative law method, the study compares the research object with similar issues in the legislation of other countries. This aspect of the methodology plays a significant role in the work. Since civil law in Georgia is influenced by continental European law, it is crucial to include countries with similar legal systems in the research. Additionally, using this method allows us to examine the experiences of common law countries, enabling a review of international approaches to the research issue and concluding which of these approaches would be most priority, flexible, and effective for Georgian legislation.